The optimal estimation algorithm of coordinate informative parameters MSK signals of packet radio with unknown initial modulation law using matching pursuit and nonlinear chirplet approximation - R. A. Volkov (Известия высших учебных заведений России: Радиоэлектроника)
New results on the recently introduced signal processing methods based on matching pursuit and modified nonlinear chirplet approximation are presented. The optimal estimation algorithm for time of arrival of MSK radio signals of packet radio in area distributed receiving points of range difference position location system is developed. The comparison of developed algorithm with known is performed.